We Have a Lot to Do: Lack of Sexual Protection and Information—Results of the German-Language Online Survey “Let's Talk About Chemsex” - Rosenberger, Cornelia; Gertzen, Marcus; Strasburger, Moritz; Schwarz, Johanna; Gernun, Solveig; Rabenstein, Andrea; Lermer, Eva; Rüther, Tobias (Frontiers in Psychiatry, 2021)
Abstract Background: The prevalence of chemsex and sexualized substance use is increasing in several European countries, particularly among men who have sex with men. In this subgroup, illegal substance use is associated with increased sexual risk behavior, which can result in severe physical and psychological impairments. The present study examined the incidence and prevalence of chemsex in German-speaking countries. Methods: To further describe the high-risk group of Chemsex users, participants (N = 429) were asked about their psychotropic substance use, sexual and health-related behavior, health status, and socio-demographic information by using an online questionnaire. Whether Chemsex has negative effects on well-being was measured with the WHO Well being Index. Of additional interest was how informed Chemsex users are about the topic and what needs are placed on the practitioners. The online questionnaire consisted of 105 items, and data was collected from March to May 2019. Results: There were no significant differences in well-being between chemsex users and non-users All participants protected themselves against sexually transmitted diseases irregularly or not at all. The majority of chemsex users reported intermittently using illegal substances (ketamine, methamphetamine, mephedrone, γ-butyrolactone/γ-hydroxy butyric acid). They viewed their sexual and substance use behavior as problematic, but few showed motivation for behavior change. Chemsex users clearly expressed a need for more information and advice centers. Conclusion: The results provide information on chemsex users that can be used for the future development of a therapy manual and thus contribute to improving health care for this group. The prevalence of chemsex is increasing and urgently needs more research to protect clients from health impairments and stigmatization.